THF cleaning for PMMA residue removal from graphene - Suutari, Sirkka (2024)
In this work the effectiveness on tetrahydrofuran cleaning on PMMA residues left behind from the polymer supported transfer process of CVD grown graphene and its ability to remove surface doping from graphene were studied. The electronic properties of the studied graphene Hall bar devices fabricated on a silicon dioxide substrate were charted during different points of the cleaning process. The amount of surface doping and the quality of the graphene was estimated using Raman spectroscopy and the amount of PMMA residues was estimated using atomic force microscopy. The electrical measurements and Raman spectroscopy showed that before cleaning the devices were highly p-doped and that the doping was reduced as a result of the cleaning. The suitability studied cleaning process for PMMA residue removal could not be conclusively estimated from the obtained results, but the process showed promise for removing ambient surface doping.